Accuracy of two-rescuer adult CPR performed by medical registrars at a South African university - Bianca Hartslief; Carmen Janse van Rensburg; Alicia Maartens; Pieter G. Marais; Erwain T. Meyer; Joleen P. Cairncross; Gina Joubert; Wilhelm Johannes Steinberg (African Journal of Emergency Medicine, 2023)
Background: Cardiopulmonary resuscitation (CPR) is performed to manually keep brain function intact until the patient's spontaneous blood circulation and breathing are restored. In South Africa, registrars, who are qualified doctors training to specialise in a medical field, are usually the team leaders and oversee junior doctors and nurses during resuscitation. Objectives: This study aimed to determine the accuracy of the execution of two-rescuer adult CPR on a Resusci-Anne® manikin performed by registrars from the University of the Free State, South Africa. Methods: A cross-sectional study was conducted. From a target population of 142 registrars, 47 participated, of whom 44 were included in the analysis. During five cycles of CPR, compression quality was assessed. During a subsequent five cycles, airway management was assessed. Participants were evaluated executing CPR on the Resusci-Anne® manikin, with a recently Basic Life Support trained student researcher as second rescuer. A modified version of the American Heart Association's tick sheet for two-rescuer adult CPR was completed by two student researchers. Department, gender and the date of the most recent CPR training attended were recorded. Results: The median total percentage score was 82.2% (range 33.3% to 100.0%). Results showed that 88.6% of registrars consistently demonstrated correct hand placement, 25.0% correct compression rate, 93.2% correct compression depth, and 61.4% allowed complete chest recoil during compressions. Consistently correct E-C technique was found in 77.3%, and correct ventilation rate in 93.2%. Only 63.6% correctly managed an open airway, and 61.4% achieved visible chest rise. A consistently correct compression-to-ventilation ratio was performed by 59.1% of registrars. Conclusion: The study found that registrars were not consistently performing high-quality CPR on a Resusci-Anne® manikin and identified areas needing attention. The results of this study highlight the need for compulsory CPR training and regular fire drills for registrars.